Decorin‐loaded poly lactic‐co‐glycolic acid nanoparticles modified by anti‐alpha fetoprotein antibody: preparation, proliferation inhibition and induced apoptosis effects on HepG2 cells in vitro. (7th March 2017) - Yang, Qiaoli; Wang, Shuyue; Wang, Yuan; Qu, Yane; Xue, Jun; Mi, Yang; Wang, Yanhong; Luo, Xuguang; Deng, Zhihua; Wang, Guiqin
Abstract: Objectives: Decorin (DCN) is a negative regulatory factor for the growth of cancer cells and can inhibit the proliferation, metastasis of cancer cells and angiogenesis in cancer tissues. The aims of this study were to prepare the nanoparticles consisting of DCN and poly lactic‐co‐glycolic acid (PLGA) modified by anti‐alpha fetoprotein (AFP) monoclonal antibody (mAb) and to examine the conventional physical properties, the in‐vitro release of DCN and the targeting effect of these nanoparticles on HepG2 cells. Key findings: The encapsulated plasmid was slowly and steadily released from the nanoparticles. The targeted PLGA nanoparticles were initiatively taken in HepG2 cells high‐efficiently. According to the results of RT‐PCR, DCN gene in AFPmAb‐PLGA‐rhDCN nanoparticles can be expressed in HepG2 cells successfully. These nanoparticles significantly inhibited the proliferation of HepG2 cells and induced apoptosis. The mRNA expression of Bcl‐2 gene in the AFPmAb‐PLGA‐rhDCN‐treated groups appeared significantly to decrease and the caspase‐3 gene had the opposite trend as compared with that of control group ( P < 0.01). Conclusion: These studies revealed that these nanoparticles were capable of specifically targeting the HepG2 cells and inhibiting the proliferation and they induce apoptosis of HepG2 cells in vitro, which was in a dose‐ and time‐dependent manner.